2003
DOI: 10.1002/ajmg.b.20109
|View full text |Cite
|
Sign up to set email alerts
|

Confirming RGS4 as a susceptibility gene for schizophrenia

Abstract: A recent study identified a putative association between variants in the regulator of G-protein signalling 4 (RGS4) and schizophrenia, Chowdari et al. [2002: Hum Mol Genet 11: 1373-1380]. RGS4 is both a positional and functional candidate gene for schizophrenia. Chowdari and colleagues identified association at this locus in a number of distinct and ethnically diverse samples, although the pattern of association was not the same in all the samples. Our study attempted to replicate this association in an indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
85
0
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(91 citation statements)
references
References 13 publications
(16 reference statements)
4
85
0
2
Order By: Relevance
“…The whole RGS4 gene was in a large LD structure, which was also supported by previous studies. 30,31 Although all the polymorphisms tested were negative, this may not be sufficient to rule out the possibility of association of other risk polymorphisms, which locate out of the strong LD structure for each gene, considering the positive evidence in previous studies. Further investigation of other at-risk polymorphisms or haplotypes, particularly exhaustive analyses at each locus, is necessary.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The whole RGS4 gene was in a large LD structure, which was also supported by previous studies. 30,31 Although all the polymorphisms tested were negative, this may not be sufficient to rule out the possibility of association of other risk polymorphisms, which locate out of the strong LD structure for each gene, considering the positive evidence in previous studies. Further investigation of other at-risk polymorphisms or haplotypes, particularly exhaustive analyses at each locus, is necessary.…”
Section: Discussionmentioning
confidence: 83%
“…For RGS4, different susceptible alleles were detected, and the risk allele frequencies were in different directions in different populations (four studies 15,30,32 reported the G allele as the risk allele but two studies 15,31 found it had the protective effect). Several possible reasons may exist for the observed discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic association between RGS4 and schizophrenia was detected initially in three different populations by Chowdari et al (20), and confirmed in five subsequent replication studies (21)(22)(23)(24)(25). However, there have been four reports of failures to replicate an association of RGS4 and schizophrenia (26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 87%
“…7 Several studies confirmed this finding. [8][9][10] A similar approach to identify candidate genes may also be effective for bipolar disorder.…”
mentioning
confidence: 99%